2007
DOI: 10.1152/physiol.00037.2006
|View full text |Cite
|
Sign up to set email alerts
|

Gene Therapy in the Treatment of Heart Failure

Abstract: Heart failure is a major cause of morbidity and mortality in contemporary societies. Although progress in conventional treatment modalities is making steady and incremental gains to reduce this disease burden, there remains a need to explore new and potentially therapeutic approaches. Gene therapy, for example, was initially envisioned as a treatment strategy for inherited monogenic disorders. It is now apparent that gene therapy has broader potential that also includes acquired polygenic diseases, such as hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 80 publications
0
35
0
1
Order By: Relevance
“…However, safety issue concerns are still restraining their use in the clinical setting: indeed, LVVs do have the potential drawback of causing insertional mutagenesis through the random integration of DNA into the host genome, leading to the aberrant expression of important genes and to tumorigenesis. 67,68 Preclinical in vivo studies have highlighted several limitations of gene therapy applications for human cardiovascular diseases: the most relevant of these regard the route of administration (LVV delivery is reviewed by Ly et al 69 ), transduction efficiency and specificity, and, most importantly, the obtainment of a functional and synchronous engraftment. In fact, arrhythmic events are often associated with cell replacement therapy of injured myocardium because homogeneous transduction of the entire myocardium is not possible and transduced cells are not uniformly distributed; engrafted cells can also fail to synchronize with the rhythm of the recipient heart.…”
Section: Final Considerationsmentioning
confidence: 99%
“…However, safety issue concerns are still restraining their use in the clinical setting: indeed, LVVs do have the potential drawback of causing insertional mutagenesis through the random integration of DNA into the host genome, leading to the aberrant expression of important genes and to tumorigenesis. 67,68 Preclinical in vivo studies have highlighted several limitations of gene therapy applications for human cardiovascular diseases: the most relevant of these regard the route of administration (LVV delivery is reviewed by Ly et al 69 ), transduction efficiency and specificity, and, most importantly, the obtainment of a functional and synchronous engraftment. In fact, arrhythmic events are often associated with cell replacement therapy of injured myocardium because homogeneous transduction of the entire myocardium is not possible and transduced cells are not uniformly distributed; engrafted cells can also fail to synchronize with the rhythm of the recipient heart.…”
Section: Final Considerationsmentioning
confidence: 99%
“…There has been particular emphasis on calcium-transport genes as candidates for gene therapy, including SERCA2a and PLB, as well as the ryanodine receptor (RyR2), and the sodiumcalcium exchanger (NCX) (Figure 1). SERCA has proven the most promising because its expression and activity are decreased in a wide variety of pathologic conditions in heart failure [12, [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…SERCA2a gene therapy has been tested in a wide variety of preclinical models, including acute ischaemia/reperfusion, chronic pressure overload and chronic myocardial infarction, has resulted in a reduction in ventricular arrhythmias experimental studies have demonstrated that gene therapy could be an effective option to treat the failing myocardium [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations